1999
DOI: 10.1021/tx980213q
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Metabolism of Nicotine and Tobacco-Specific N-Nitrosamines to 4-Hydroxy-4-(3-pyridyl)butanoic Acid in Rats

Abstract: The carcinogenic tobacco-specific nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N'-nitrosonornicotine (NNN) are believed to play a role in cancers associated with the use of tobacco products. Urinary metabolites of NNK and NNN could be used as biomarkers for an individual's ability to metabolically activate or detoxify these nitrosamines. While several metabolites of NNK can be quantified in human urine, no assay is available to determine human urinary levels of NNK and NNN metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
1
27
2
Order By: Relevance
“…In this context, only 1.1% of [5-3 H]keto acid i.v. administered to F344 rats was metabolized to hydroxy acid, whereas 94.8% of the keto acid was excreted unmetabolized (Trushin and Hecht, 1999). In case that hydroxy acid is exclusively formed from keto acid, the percentage expected in myosmine metabolism would be approximately 0.5% of all metabolites and therefore below the detection limit in the present study.…”
Section: Metabolism Of Myosmine In Ratscontrasting
confidence: 56%
“…In this context, only 1.1% of [5-3 H]keto acid i.v. administered to F344 rats was metabolized to hydroxy acid, whereas 94.8% of the keto acid was excreted unmetabolized (Trushin and Hecht, 1999). In case that hydroxy acid is exclusively formed from keto acid, the percentage expected in myosmine metabolism would be approximately 0.5% of all metabolites and therefore below the detection limit in the present study.…”
Section: Metabolism Of Myosmine In Ratscontrasting
confidence: 56%
“…Peak 1 was identified as the hydroxy acid by coelution with a standard. The assignment was confirmed by converting the urinary hydroxy acid to its methyl ester then allowing it to react with (S)-(Ϫ)␣-methylbenzyl isocyanate, as described previously (Trushin and Hecht, 1999). The resulting carbamate diastereomers coeluted with standards.…”
Section: Fig 4 Gc-positive Ion Ci-ms Analysis Of Materials Obtained mentioning
confidence: 89%
“…Since nicotine levels in tobacco products are as much as 10,000 times greater than those of NNN, the hydroxy acid and keto acid cannot be used as specific biomarkers of NNN uptake Trushin and Hecht, 1999). Metabolites of NNN that retain unique structural features related to NNN, such as NNN-N-oxide, 3Ј-hydroxyNNN, and 4Ј-hydroxyNNN, are relatively minor urinary metabolites in rodents.…”
Section: Nnnmentioning
confidence: 99%
“…HA is the most abundant NNK metabolite detected in urine and it is also produced during N ¶-nitrosonornicotine and nicotine metabolism (33)(34)(35). However, the formation of HA from N ¶-nitrosonornicotine and nicotine is not accompanied with N 7 -MeG generation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the formation of HA from N ¶-nitrosonornicotine and nicotine is not accompanied with N 7 -MeG generation. It has been shown that 12% of urinary HA is generated from NNK, 31% from N ¶-nitrosonornicotine, 1% from keto acid, and only 0.1% from nicotine in rats (33). More recently, Stepanov et al (36) showed that the levels of NNKderived HA were much higher than the levels of total NNAL in smokers.…”
Section: Discussionmentioning
confidence: 99%